Assessment of Maternal Health Knowledge and Access to Maternal Health Information among Mothers in Windhoek - Aku-Akai , Larai (Recent Updates in Disease and Health Research Vol. 2, 2024)
Introduction: Maternal and neonatal morbidity and mortality occurs due to unexpected obstetric emergencies, and by delays in recognizing complications, seeking and receiving care for these complications. Knowledge regarding pregnancy risk factors and warning signs in pregnancy is a major contributor to delayed response and maternal health seeking behaviour. This study aimed to assess maternal health knowledge and access to maternal health information among mothers in Windhoek. Methods: A cross-sectional, pilot study was done with 56 women and 30 health workers. Data was collected with questionnaires, and analysed using SPSS version 28, in descriptive and inferential statistics, presented in tables and charts. Ethical approval and informed consent were obtained; confidentiality, anonymity and privacy were maintained; participation was voluntary. Results: The study revealed that almost half of the women (46.4%) have average knowledge regarding maternal health issues. All women mentioned at least 1 danger sign (100%) and most women mentioned 2 or more danger signs (96.0%), unprompted. Most women had access to maternal health information, mainly through access to health facilities/health workers (72.2%), antenatal clinics (26.6%) and informal channels such as family members (11.4%) and social media (15.2%). Challenges reported in accessing maternal health information was that information sources often had insufficient reach, was difficult to understand, and often not in local languages. Information from informal sources was often unreliable, misleading and contradictory. These indicate maternal health information gaps that need to be addressed to improve access to useful information to pregnant women. Conclusion: Findings indicated opportunity to scale up dissemination of relevant maternal health information through suitable media, made universally acceptable and accessible to all women in an equitable and individualised manner. It highlights the need to strengthen, diversify and simplify health messages and language used therein, thereby increasing the reach of maternal health information through diverse media, to positively influence birth preparedness and maternal health seeking behaviour.